(untitled) (Informatica, 2024)
Recently, Big data analysis has been a very active research area with a significant impact on industrial and scientific domains. Thus, the security of big data provides the conditions for securing and monitoring cloud applications that need protect highly sensitive data hosted in cloud platforms. Nevertheless, the big data security issues have become increasingly problematic, leading organizations to restrict the utilization of cloud services. The existing security methods have revealed several issues, including a weakness of data security and Inaccuracy in data analysis, inefficiencies in performance and dependence on a third party. To address these issues, this study proposed a simpler technique as known a triple-data encryption standard (3DES) through providing the long keys sizes in Data Encryption Standard (DES) to protect the privacy of data against the potential attack in cloud computing environments. The experimental results confirm the efficiency of the proposed method in enhancing the secure of big healthcare data storage in cloud computing environment with less computational time compared to the existing method of Intelligent Framework for Healthcare Data Security. In conclusion, the proposed 3DES is recommended as a candidate encryption and decryption method in healthcare applications in cloud computing environments